Session-to-session variations in external load measures during small-sided games in professional soccer players - Saeid Younesi; Alireza Rabbani; Filipe Clemente; Hugo Sarmento; António J. Figueiredo (Termedia Publishing House, 2020)
The aims of this study were 1) to analyse session-to-session variations in different external load measures and 2) to examine differences in within-session intervals across different small-sided game (SSG) formats in professional players. Twenty professional soccer players (mean ± SD; age 28.1 ± 4.6 years, height 176.7 ± 4.9 cm, body mass 72.0 ± 7.8 kg, and body fat 10.3 ± 3.8%) participated in 3v3, 4v4, and 6v6 SSGs under different conditions (i.e., touch limitations and presence of goalkeepers vs. free touch and ball possession drill) over three sessions. Selected external load measures-including total distance (TD), high- intensity running (HIR, distance covered > 14.4 km.h-1), high-speed running (HSR, distance covered > 19.8 km.h-1), and mechanical work (MW, accelerations and deceleration > 2.2 m.s2)-were recorded using GPS technology during all SSG sessions. Small to large standardized typical errors were observed in session-to-session variations of selected measures across SSGs. TD.min-1 showed less variability, having a coefficient of variation (CV) of 2.2 to 4.6%, while all other selected external load measures had CV values ranging from 7.2% to 29.4%. Trivial differences were observed between intervals in TD.min-1 and HIR.min-1 for all SSGs, as well as in HSR.min-1 and MW.min-1 for most SSG formats. No reductions or incremental trends in session-to-session variations were observed when employing touch limitations or adding goalkeepers. The increased noise observed in higher speed zones (e.g., high-speed running) suggests a need for more controlled, running-based conditional drills if the aim is greater consistency in these measures.